Total Synthesis of Marine Macrolide Natural Products by the Macrocyclization/Transannular Pyran Cyclization Strategy - Fuwa, Haruhiko (Synlett, 2023)
In this Account, we summarize the development of a new strategy for streamlined synthesis of tetrahydropyran-embedded macrolactones and its successful implementation to a 13-step synthesis of (–)-exiguolide and an 11-step synthesis of (+)-neopeltolide.1 Introduction2 Development of Macrocyclization/Transannular Pyran Cyclization Strategy3 Total Synthesis of (–)-Exiguolide4 Total Synthesis of (+)-Neopeltolide5 Conclusions
Keywords: synthetic methods; tandem reactions; total synthesis; macrolides; step-economy